ANALYSIS OF THE RESPONSIBILITY OF GOVERNMENT INSTITUTIONS IN RETURNING STATE LOSSES ACCORDING TO LAW NUMBER 30 OF 2014 ON GOVERNMENT ADMINISTRATION - Krisnamurti, Joseph Harry; Gunawan, Belinda (Badan Pemeriksa Keuangan Republik Indonesia, 2019)
The passage Law Number 30 of 2014 on Government Administration has raised its own problems due to its clauses regarding legal subjects that could be charged with reinstating state losses. This is due to the fact that such Law provides that government institutions can be determined as the party that is responsible for reinstating state loss that have occurred, which contradicts with the definition of state loss as stipulated in the applicable state finance laws that position the state as the party suffering the loss when a state loss is incurred. This research has been conducted using a normative legal research method which aims to test consistency between the legal norms applied in Law Number 30 of 2014 and the laws on state finance. Result of this research demonstrates that government institutions cannot be designated as the legal subject responsible for state losses. Such stipulation is not legally logical as it asserts that government institutions that are in fact representatives of the State may be required to return or pay the state losses to the state. Therefore there needs to be a revision to the relevant provisions of Law Number 30 of 2014 in order for such law to be in line with the provisions that presently govern state finance.